2004
DOI: 10.1007/s10517-005-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective accumulation of monoclonal antibodies against neurospecific enolase in brain tissue of rats with middle cerebral artery occlusion

Abstract: Preparations of I(125)-labeled monoclonal antibodies against neurospecific enolase and mouse plasma IgG1 were injected intravenously to rats immediately after unilateral occlusion of the middle cerebral artery. Radioactivity of I(125)-labeled monoclonal antibodies against neurospecific enolase in the brain tissue progressively increased, reached a maximum by the 48th hour, and remained practically unchanged after 72 h. At the same time radioactivity of labeled IgG1 in the brain tissue and radioactivity of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our data show a reduced postischemic neuronal death in vivo by TLR2 inhibition in a standard experimental stroke model. We applied TLR2-blocking antibody after MCAO to mimic a potential therapeutical use and because of speculated postischemic breakdown of the blood-brain barrier (Belayev et al, 1996), which should improve the ability of the antibodies to reach their target cells (most probably macrophages/monocytes and microglia), as shown in a rat MCAO model (Chekhonin et al, 2004). The relative large variability in the stroke volumes obtained in knockout mice compared with wild-type mice ( Figure 1A) suits similar findings in other knockout mice (Harhausen et al, 2010;Trendelenburg et al, 2002;Ziegler et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show a reduced postischemic neuronal death in vivo by TLR2 inhibition in a standard experimental stroke model. We applied TLR2-blocking antibody after MCAO to mimic a potential therapeutical use and because of speculated postischemic breakdown of the blood-brain barrier (Belayev et al, 1996), which should improve the ability of the antibodies to reach their target cells (most probably macrophages/monocytes and microglia), as shown in a rat MCAO model (Chekhonin et al, 2004). The relative large variability in the stroke volumes obtained in knockout mice compared with wild-type mice ( Figure 1A) suits similar findings in other knockout mice (Harhausen et al, 2010;Trendelenburg et al, 2002;Ziegler et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The same antibody was used to block TLR2-mediated activation of monocytes by Pneumocystis murina in vitro (Zhang et al, 2006). Recently, it was shown that intravascular applied monoclonal antibodies permeate rodent brain after induction of focal cerebral ischemia (Chekhonin et al, 2004). However, there is no information about therapeutical use of TLR2 inhibitors in cerebral ischemia in vivo up to now.…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 defective mice were shown to be protective against ischemic stroke in several investigations [ 107 , 108 , 109 , 110 ]. Following the establishment of localized cerebral ischemia, intravascularly administered monoclonal antibodies penetrate the rodent brain [ 111 ]. The anti-inflammatory impact of TLR4-inhibition in experimental stroke was specifically established by the administration of TLR4 blocking antibody (mAbs clone MTS510) in vivo [ 112 ] ( Table 2 ).…”
Section: Application Of Antibody-based Drugs For Cerebral Ischemiamentioning
confidence: 99%